Development and validation of the facilitative interpersonal skills scale for clients. Issue 4 (2nd December 2022) - Santos, João M.; Barata, Matilde; Rathenau, Sara; Amaro, Inês; Vaz, Alexandre; Sousa, Daniel; Severino, Margarida; Taveira, Mafalda
Abstract: Objective: Psychotherapy studies have revealed that therapist characteristics are responsible for 5% to 9% of outcome variance. The therapist‐facilitative interpersonal skills (FIS) have been shown to predict both alliance and outcomes, indicating that higher FIS therapists are more effective than lower FIS therapists. The current study focused on the development and validation of the FIS‐client version (FIS‐C) instrument, aimed at collecting the clients' perspectives on relevant therapist characteristics. Method: The clinical outcomes in routine evaluation—outcome measures, the session rating scale, and the FIS questionnaire—client version were filled out by psychotherapy clients. Exploratory, confirmatory factor, and test–retest analysis were conducted. Results: Results indicate robust psychometric characteristics, in terms of validity (factorial, convergent, discriminant, and nomological), reliability, and sensitivity. Conclusion: The validation of the FIS‐C represents an important contribution to clinical research and practice, namely to the field of client feedback and therapist expertise.